An experimental-numerical study of heat transfer enhancement in a minichannel using asymmetric pulsating flows - O'Shaughnessy, Seamus (My University, 2023)
The development of current and next generation high performance electronic devices has led to miniaturization in more densely packed spaces. The increasing power levels has resulted in ever-increasing heat flux densities which necessitates the evolution of new liquid-based heat exchange technologies. Implementation of single-phase cooling systems using pulsating flow is viewed as a potential solution to the problems involving high energy density electronics. This work involves a combined experimental and numerical analysis of pulsating flows in a rectangular minichannel undergoing asymmetric sinusoidal flow pulsation formats. The minichannel design includes a heated bottom section approximated as a constant heat flux boundary by uniformly heating a 12.5 μm thick Inconel foil. Infrared thermography (IR) is used for thermal measurements of the heated boundary from the hydrodynamically and thermally developed region of the minichannel. A three-dimensional conjugate heat transfer ANSYS CFX model is used for simulations. Asymmetric sinusoidal pulsating flows in the form of leading and lagging profiles with Womersley number of 2.5 and a flow rate amplitude ratio of 0.5 and 3 are investigated. The rapid fluctuating characteristics of the asymmetric waveforms cause a sudden shift in the flow velocity profiles and the subsequent increased pressure drop shows an evolution of phase lag. The intensification of fluid momentum due to high oscillating flowrate amplitudes causes enhanced mixing in the near-wall and bulk regions of the channel, as evidenced by the wall temperature profiles. The presence of wall viscous forces leads to the phenomenon of annular effects which has been widely investigated in the literature for symmetric flow profiles. The wall and bulk temperature profiles tend to readily adjust to this rapidly fluctuating flow. The effect of high pulsation flow rate amplitude leads to a heat transfer enhancement of about 11% over the corresponding steady flow.
2023 22nd IEEE Intersociety Conference on Thermal and Thermomechanical Phenomena in Electronic Systems (ITherm) 30 May-2 June 2023 2023
Keywords: Heat transfer enhancement; Flow rate modulation; Conjugate heat transfer; Oscillating flow; Pulsating flow; Smart & Sustainable Planet; Applied thermodynamics and energy; Computational Fluid Dynamics; Design Engineering; ENERGY; Electronics Cooling; Fluid Dynamics; Mechanical Engineering; Thermal Engineering; minichannels; pulsating flow